Peace child - Richardson, Don; Forsberg, Rolf; Tizzard, Edward G.; Roberts, Fred A.; Gospel Communications International (Muskegon, MI : Gospel Communications International, 1972)
Don and Carol Richardson respond to the call of Christ. Careful preparation for their mission and a journey by dug-out canoe bring them to a remote rain forest inhabited by some of the world's most primitive people. Painstakingly, they learn the language only to be shocked when the story of Judas' betrayal of Jesus makes him a hero to a people whose highest attribute is to be masters of treachery. When inter-tribal warfare breaks out, the battles continue until a warring chief offers his son as a means of bringing lasting peace. This primitive tribal custom makes the Gospel understandable. lives are changed. A church appears.
Peace child is an exceptional film blending ferocious inter-tribal warfare, expert cinematography, and Christian compassion in a dramatic re-creation of a classic missions success story.
[Based on the book Peace Child by Don Richardson, Regal Books]
Originally released as videorecording in 1974
"An excellent film on evangelism and missions, translated in English, Tagalog, Cebuano, Ilocano-- and a lot more." -- container
Keywords: Richardson, Don, 1935--; Richardson, Carol; Missions -- Indonesia